Scale-Up of Voluntary Medical Male Circumcision Services for HIV Prevention — 12 Countries in Southern and Eastern Africa, 2013–2016 - Hines, Jonas Z.; Malaba, Kananga; Zegeye, Tiruneh; June, Elijah Odoyo; Nyirenda, Rose Kolola; Mutandi, Gram; Yoboka, Emmanuel; Maringa, Hilda; Simbeye, Daimon; Kazaura, Kokuhumbya; Lubwama, Joseph; Kabuye, Geoffrey; et al. (Morbidity and Mortality Weekly Report, 2017)
Countries in Southern and Eastern Africa have the highest prevalence of human immunodeficiency virus (HIV) infection in the world; in 2015, 52% (approximately 19 million) of all persons living with HIV infection resided in these two regions.* Voluntary medical male circumcision (VMMC) reduces the risk for heterosexually acquired HIV infection among males by approximately 60% (1). As such, it is an essential component of the Joint United Nations Programme on HIV/AIDS (UNAIDS) strategy for ending acquired immunodeficiency syndrome (AIDS) by 2030 (2). Substantial progress toward achieving VMMC targets has been made in the 10 years since the World Health Organization (WHO) and UNAIDS recommended scale-up of VMMC for HIV prevention in 14 Southern and Eastern African countries with generalized HIV epidemics and low male circumcision prevalence (3).† This has been enabled in part by nearly $2 billion in cumulative funding through the President’s Emergency Plan for AIDS Relief (PEPFAR), administered through multiple U.S. governmental agencies, including CDC, which has supported nearly half of all PEPFAR-supported VMMCs to date. Approximately 14.5 million VMMCs were performed globally during 2008–2016, which represented 70% of the original target of 20.8 million VMMCs in males aged 15–49 years through 2016 (4). Despite falling short of the target, these VMMCs are projected to avert 500,000 HIV infections by the end of 2030 (4). However, UNAIDS has estimated an additional 27 million VMMCs need to be performed by 2021 to meet the Fast Track targets (2). This report updates a previous report covering the period 2010–2012, when VMMC implementing partners supported by CDC performed approximately 1 million VMMCs in nine countries (5). During 2013–2016, these implementing partners performed nearly 5 million VMMCs in 12 countries. Meeting the global target will require redoubling current efforts and introducing novel strategies that increase demand among subgroups of males who have historically been reluctant to undergo VMMC.
Keywords: HIV Prevention; Medical Male Circumcision Services; Scale-Up